2013
DOI: 10.1093/erae/jbt006
|View full text |Cite
|
Sign up to set email alerts
|

Expected utility or prospect theory maximisers? Assessing farmers' risk behaviour from field-experiment data

Abstract: We elicit the risk preferences of a sample of French farmers in a field-experiment setting, considering both expected utility and cumulative prospect theory. Under the EU framework, our results show that farmers are characterised by a concave utility function for gain outcomes implying risk aversion. The CPT framework confirms this result, but also suggests that farmers are twice as sensitive to losses as to gains and tend to pay undue attention to unlikely extreme outcomes. Accounting for loss aversion and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 93 publications
15
152
1
2
Order By: Relevance
“…Second, we followed a protocol similar to those used in other experimental papers. Several scaling factors that have already been used in the literature are 2% in Bocquého et al (2014), 10% in Abdellaoui et al (2008) and 1/600 in Galarza (2009). Scaling the displayed earning amounts, however, does make it difficult to know with certainty whether subjects made their decisions based on the high amounts that were displayed or the lower amounts that were actually to be paid at the end of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we followed a protocol similar to those used in other experimental papers. Several scaling factors that have already been used in the literature are 2% in Bocquého et al (2014), 10% in Abdellaoui et al (2008) and 1/600 in Galarza (2009). Scaling the displayed earning amounts, however, does make it difficult to know with certainty whether subjects made their decisions based on the high amounts that were displayed or the lower amounts that were actually to be paid at the end of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The 3-parameter value function in Equation (1) differs from the models usually estimated in the literature. Indeed, most studies involving a structural estimation of risk parameters (Bocquého et al, 2014;Tanaka et al, 2010) assume that α + = α − . In order to facilitate a comparison of our results with the existing literature, we make the same assumption that α = α + = α − , as well as the assumption that ρ = ρ + = ρ − (see Section 4.1).…”
Section: Lottery Choice Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies (Tanaka et al 2010;Bocqueho et al 2014) document potential empirical support for prospect theory (PT, Kahneman and Tversky (1979)) 3 when it comes to risk attitudes: Harrison et al (2010) found that PT describes behavior of half of their sample best. There is also evidence that subjective probability weighting (PW) (Quiggin 1982) should be taken into account.…”
Section: Multiple Price Lists Explainedmentioning
confidence: 99%
“…Much of the scientific debate in agricultural decision (or risk) analysis has been on the assessment of the risk attitude (or preferences), which is reflected by the shape of the utility function. Nowadays, the proposed s-shaped utility function from cumulative prospect theory is also tested (Bocquého et al, 2013;Franken et al, 2014). Less attention is given to how farmers make judgments about probabilities and consequences of uncertain events (Lybbert and Just, 2007;Hardaker and Lien, 2010;Just et al, 2010).…”
Section: Understanding How Farmers Cope With Riskmentioning
confidence: 99%